Biofilm-forming ability of Staphylococcus aureus on materials commonly found in milking equipment surfaces - C. Medina; D. Manriquez; B.A. Gonzalez-Córdova; P.A. Pacha; J.M. Vidal; R. Oliva; A.A. Latorre (Journal of Dairy Science)
ABSTRACT: The presence of biofilms on milking equipment on dairy farms can be a source of bulk tank milk contamination, as well as a potential source of intramammary infections for cows. The biofilm-forming ability of bacteria, including Staphylococcus aureus, may differ depending on factors such as the intrinsic ability of bacteria to form biofilms, as well as the roughness and type of material of the surfaces. We investigated the ability of S. aureus to form biofilms on coupons made of stainless steel, nitrile (or Buna-N) rubber, ethylene propylene diene monomer (EPDM) rubber, silicone rubber, borosilicate glass, polycarbonate, and polyvinyl chloride, which are materials commonly used to manufacture pieces of milking equipment. Three S. aureus strains isolated from biofilms naturally formed in milking equipment on dairy farms, and previously characterized for high, medium, or low adherence ability by microtiter plate assay, were analyzed to assess their ability to form in vitro biofilms using a CDC Biofilm Reactor (Biosurface Technologies, Bozeman, MT). Bacterial counts of suspended biofilms and scanning electron microscopy were performed on coupons of each material. The highest bacterial counts were observed in Buna-N surfaces for high-adherence (L1-1171, mean = 4.54 log10 cfu/mL), medium-adherence (L1-030, mean = 4.18 log10 cfu/mL), and low-adherence (L1-256, mean = 3.71 log10 cfu/mL) S. aureus. The biofilm-forming ability for the same S. aureus strain, regardless its adherence abilities, was not significantly different among all tested surface materials, except Buna-N rubber, for which all 3 strains had an increased ability to form biofilms. In the same material, no statistically significant differences were observed among strains, except for Buna-N and EPDM rubber, in which the highly adherent S. aureus strain (L1-1171) had greater biofilm formation as compared with other strains. Regular replacement of rubber parts of milking equipment is warranted to reduce the risk of biofilm formation.